Governança florestal via comércio internacional de madeira: políticas da União Europeia e suas influências nos atores sociais do Brasil - LIMA, Rayssa Yuki Murakami (Universidade Federal do Pará, 2025)
Following the international trend towards sustainable and illegality-free production chains, the European Union (EU) has adopted its own policies and strategies that potentially impact countries such as Brazil, which produce a large part of the commodities consumed by the EU, including timber. In this sense, the objective of this study is to understand how ready Brazilian governance of the tropical native forest sector is to respond to the demands of this trend, based on domestic policies and strategies, as well as on the network of interaction and influence of its stakeholders. To meet this objective, a systematic review was first used using the PRISMA-P protocol to identify Brazilian and international instruments for promoting legality and sustainability in the timber sector. Next, a situational analysis was carried out to assess in detail the possible impacts of the EU Regulation for Deforestation-Free Products (EUDR) on the forest scenario in Brazil. Finally, the network analysis served to understand how the relationships and influence strategies of stakeholders in the Brazilian forest sector (government, private sector, civil society and academia) affect Brazilian governance in the international scenario. Our results indicate that Brazil is well positioned regarding instruments, particularly state-owned instruments, since they have synergies with each other and with international instruments in the same area. However, the effective implementation of these instruments remains the country's main challenge. In addition to correcting these shortcomings, the application of a policy mix and/or hybrid strategies based on national instruments would be necessary. Additionally, dialogue, cooperation and mutual accountability between producing and consuming countries, as well as economic incentives, are recommended. These recommendations are also valid for Brazil's alignment with the EUDR, since the country may face risks associated, above all, with legal and governance aspects (e.g: inconsistencies between EU standards and Brazilian environmental laws), economic (e.g: unequal distribution of additional costs) and socio-environmental (e.g: shifts to less regulated markets). On the other hand, the EUDR also offers opportunities for Brazil to strengthen its sustainability instruments and policies by seeking to maintain its exports to the EU. In the perception of stakeholders in the Brazilian forestry sector, the Regulation brings together more negative than positive perceptions and the networks of relationships and influences formed by them showed little connectivity. Furthermore, we identified asymmetries regarding the influence strategies of the determined focus groups: the federal government and the private sector tended towards influence strategies of direct retention of resources (e.g: direct control of information for decision-making), while civil society and academia tended towards indirect retention and indirect use strategies, respectively. We conclude that Brazilian forest governance has structures that are partially aligned with international sustainability and legality requirements. Brazil has good instruments in this sense, and they are connected to the needs of international governance, but it needs to improve their domestic implementation to be effective. The network of stakeholders needs to strengthen its cohesion and connectivity to improve its forms of influence on forest governance beyond the individual interests of groups. To remain a relevant player in the commodities trade, Brazil faces the challenge of adapting and improving its forest governance to the strict international demands for sustainability, such as European policies, overcoming historical illegalities in the timber production chain, improving existing instruments and strengthening the network of stakeholders. Consumer countries that have already been complicit in the problem by importing products of illegal origin should consider supporting producer countries in adapting their production methods to reduce socioenvironmental risks.